PENGARUH WAKTU FERMENTASI DAN EFEKTIVITAS ADSORBEN DALAM PEMBUATAN BIOETANOL FUEL GRADE DARI LIMBAH POD KAKAO (THEOBROMA CACAO) - A. Rachman Fauzi; Didik Haryadi; Slamet Priyanto (Jurusan Teknik Kimia, Fakultas Teknik, Universitas Diponegoro, 2012)
The scarcity of fuel oil globally will need to use biofuels as a alternative fuel. One of it is bioethanol. Bioethanol is ethanol produced from sugar fermentation. Generally bioethanol made from crops like sugar cane and sweet sorghum. Though the plant has a use value as food. This can cause food prices creeping up highly interest in plants and biofuel producers to process the material into bioethanol. Cocoa plantation commodities whose role is quite important to the national economy. Components of the cocoa pod waste is the largest cocoa pod which is 75%. The cocoa pod has a coarse fiber which consists of 27,8278 % lignin, 22,852 % cellulose,and 11,9482 % hemicellulose. The content of cellulose and hemicellulose in the cocoa pod can be further processed into bioethanol by hydrolysis, fermentation, distillation and adsorption (purification). Method for the purification of bioethanol used adsoption, to separate water from ethanol compound. The study was conducted using experimental methods and performed in the laboratory of chemical engineering, University of Diponegoro. Phases of the study are preparation materials, hydrolysis, fermentation, distillation, adsorption, and analysis of results. Variables change at the time of fermentation experiments (144: 168: 192: 216) hours, but it's kind of adsorbent during the distillation of molecular sieve 3A, silica gel and a mixture of molecular sieve 3A and silica gel. Variables fixed at the stage of hydrolysis is 100 grams of cocoa pod powder, 2N H2SO4, 1 liter distilled water, 4 hours of hydrolysis time, hydrolysis temperature 100OC. Variables fermentation stage are 0.23% w S. cerevisiae, 18% glucose, 0.5% w Urea, 0.06% w NPK, pH 5. At this stage of the distillation temperature of 85 °C, the volume of 60 ml, 1.5-hour distillation time and at this stage of dehydration is 90gram weight of adsorbent, temperature 78OC. Responses were observed levels of ethanol that is produced on fermentation time and the ability of molecular sieve 3A or silica gel in ethanol purification. The result showed that the fermentation of the cocoa pod is the best at 168 hours. Molecular sieve 3A is a better adsorbent than silica gel or molecular sieve 3A + mixture of silica gel. Fuel grade ethanol is obtained by the adsorption of the ethanol content of 95.87% to 99.16% using molecular sieve 3A.